2020
DOI: 10.1111/aec.12951
|View full text |Cite
|
Sign up to set email alerts
|

Decline in lizard species diversity, abundance and ectoparasite load across an elevational gradient in the Australian alps

Abstract: The rapid changes in altitude, and associated habitat, of mountain ecosystems make them ideal natural laboratories for testing the effect of environmental heterogeneity on species assemblage. Our understanding of the sensitivity of Australian reptiles to elevational clines is limited. We examined lizard distribution across three elevation zones (montane, subalpine and alpine), spanning from 900 to 1840 m above sea level, in the Australian alps. We aimed to examine how elevation influences species diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…This latter study highlighted that each host-parasite system showed unique particularities, despite involving related hosts in similar environments. An inverse relationship was also described between different habitats for both parasites, with mites being more present in areas with dry grasslands and little disturbance, and ticks in areas with higher plant cover and disturbance by livestock [39]. Our results corroborate this-even in a simplified island system, unique particularities are seen between different ectoparasites and endoparasites.…”
Section: Discussionsupporting
confidence: 86%
“…This latter study highlighted that each host-parasite system showed unique particularities, despite involving related hosts in similar environments. An inverse relationship was also described between different habitats for both parasites, with mites being more present in areas with dry grasslands and little disturbance, and ticks in areas with higher plant cover and disturbance by livestock [39]. Our results corroborate this-even in a simplified island system, unique particularities are seen between different ectoparasites and endoparasites.…”
Section: Discussionsupporting
confidence: 86%
“…Here, we examined the effects of parasitism on whole‐organism performance (in particular locomotor performance and foraging efficiency) and thermal preference in common garden skinks ( Lampropholis guichenoti ). Garden skinks are host to several gastrointestinal parasites, Eimeria lamkpropholidus (Cannon, 1967), Cylindrotaenia hickmani (Goldberg & Bursey, 2012; Jones, 1985), Skrjabinodon sp., Maxvachonia chabaudi , Hedruris wogwogensis (Jones & Resasco, 2016), Sphaerechinorhynchus rotundocapitatus (Daniels & Simbotwe, 1984), as well as ectoparasites including mites (Trombiculidae) and hard ticks (Acari: Ixodida; Hamilton et al, 2021). However, the effects of these parasites on their host are poorly understood (Resasco et al, 2019).…”
Section: Introductionmentioning
confidence: 99%